Machine dreaming: an environmental perspective. (3rd March 2005) - Juniper, James
Mirowski's Machine Dreaming provides an invaluable critical history of the post-war development of economic theory under the influence of military-funded Cold War research into the cybernetic sciences. However, this reviewer argues that in restricting the scope of his historical analysis to the influence of the natural sciences over the development of economic thought, Mirowski has neglected a variety of traditions within cybernetics and systems theory that draw on the philosophy of language. Moreover, the paper traces the influence these neglected traditions have exerted over various strands of economic analysis. Finally, these strands of economic theory are interrogated to identify various ways they have influenced the development of richer and more comprehensive notions of environmental sustainability.